Псевдоiнверсний пiдхiд до розв’язання одного класу нелiнiйних алгебраїчних рiвнянь - Стоян, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
The problem of the root-mean-square inversion of the systems of nonlinear equations, whose left part is the Cartesian product of the set quantity of linear algebraic transformations, is solved. The conditions of exactness and unambiguity of the given solution are defined.